2014
DOI: 10.2147/ijn.s57875
|View full text |Cite
|
Sign up to set email alerts
|

Inhibited bacterial biofilm formation and improved osteogenic activity on gentamicin-loaded titania nanotubes with various diameters

Abstract: Titania nanotubes loaded with antibiotics can deliver a high concentration of antibiotics locally at a specific site, thereby providing a promising strategy to prevent implant-associated infections. In this study we have fabricated titania nanotubes with various diameters (80, 120, 160, and 200 nm) and 200 nm length via electrochemical anodization. These nanotubes were loaded with 2 mg of gentamicin using a lyophilization method and vacuum drying. A standard strain, Staphylococcus epidermidis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“… 12 Our previous in vitro and in vivo studies revealed that gentamicin-loaded nanotubes on titanium substrates exhibited evident antibacterial activity for the two bacterial strains mentioned above. 13 , 14 However, the resistance to β-lactamase, aminoglycoside, lincosamide, trimethoprim, macrolide, tetracycline, and sulfonamide antibiotics in S. aureus and S. epidermidis is widespread in current orthopedics surgery. 15 , 16 Therefore, implants with good antibacterial capability, especially under methicillin-resistant stapthylococci infection, is critical to the successful fixation and healing of bone fractures in current orthopedic surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 Our previous in vitro and in vivo studies revealed that gentamicin-loaded nanotubes on titanium substrates exhibited evident antibacterial activity for the two bacterial strains mentioned above. 13 , 14 However, the resistance to β-lactamase, aminoglycoside, lincosamide, trimethoprim, macrolide, tetracycline, and sulfonamide antibiotics in S. aureus and S. epidermidis is widespread in current orthopedics surgery. 15 , 16 Therefore, implants with good antibacterial capability, especially under methicillin-resistant stapthylococci infection, is critical to the successful fixation and healing of bone fractures in current orthopedic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Although the in vitro antibacterial activity of HACC-loaded nanotubes with a diameter of 200 nm was reported to be better than those with a diameter of 160 nm, 24 the cytocompatibility had a negative correlation with the diameter of the nanotubes. 13 Therefore, we fabricated TNTs with 160 nm diameters on titanium plates and rods for the consideration of both the antibacterial capability and cytocompatibility in this study. Quaternized chitosan with a degree of substitution of 26% was loaded into these nanotubes to form an effective local antibiotic delivery system, and the in vitro cytocompatibility was assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium alloys, mainly Ti-6Al-4V, are commonly used in orthopedic surgery and traumatology due to their well-known physico-chemical properties and biocompatibility (16)(17)(18). To date, most of the methods used to manufacture nanotubular oxide layers with potential biomedical applications have been implemented in pure titanium (19)(20)(21)(22)(23)(24)(25)(26). Recently, we demonstrated that fluorine (F) doping during the anodizing process of Ti-6Al-4V decreases staphylococcal adherence by about 50% (27) and that F doping, together with the nanostructure resulting from the anodizing process, improves the osseointegrative properties by favoring matrix mineralization of osteoblastic cells (28).…”
mentioning
confidence: 99%
“…They also tested the osteogenic differentiation ability of the prepared gentamicinloaded nanotubes using human marrow derived mesenchymal stem cells; their results revealed significantly promoted cell attachment, proliferation, spreading, and osteogenic differentiation when compared to titania. Then results also showed the efficiency of titania nanotubes loaded with antibiotics for local delivery to a specific site and presenting a promising strategy to prevent implantassociated infections (50).…”
Section: Nanoparticlementioning
confidence: 95%